How school life with international students develops the intercultural competence of domestic dental students. (4th January 2022) - Oka, Hiroko; Taji, Tsuyoshi
Abstract: Introduction: Reflecting multicultural society, the diversity of the healthcare professional students' ethnicities and cultures is promoted around the world. However, most of the healthcare professional education in Japan had been targeted mainly at students who follow the Japanese language and culture. The aim of this study is to clarify what Japanese dental students have culturally experienced and how they developed intercultural competence during their school life with international dental students in Japan. Materials and Methods: We conducted semi‐structured interviews with 18 of the sixth‐grade students in standard Japanese undergraduate dental programmes who shared required classes in Japan with non‐Japanese‐speaking international dental students in preclinical programmes. Based on the qualitative analysis of the interviews, we administered a questionnaire survey to 82 dental trainees (the seventh grade) in clinical training programmes who just graduated from various Japanese dental schools. Then, the answers of the questionnaire were statically analysed. Results: The interview identified a total of 37 constituent elements regarding "students' attitudes and experiences in school days" and "perceptions and motivations." Analysis of the questionnaire showed that the group experiencing a learning environment with international students had various communication with and respect for their various classmates and had the ambition to develop themselves. Especially, the participants who had international experiences both in and out of classrooms showed more active attitude on intercultural communication. Conclusions: Overall, for Japanese dental students, daily contact with international students gave direct and indirect cross‐cultural experiences and recognitions. In particular, the Japanese students were stimulated active perceptions. The findings of this study can be used for future discussion about the cross‐cultural education and collaboration of healthcare professionals not only within Japan but also around the world.